O Porto sentido pelo graffiti: as representações sociais de peças de graffiti pelos habitantes da cidade do Porto - Torre, Elena de la (2016)
We try to analyze the representations of different graffiti pieces located in the city of Porto, Portugal, focusing the city dwellers perspective. Graffiti has been approached from diverse disciplinary points of view and frequently from the lenses of its protagonists. For that reason, it is considered that it is required to analyze the way by which others, the ones that ignore the style and symbolic codes of graffiti production, think and envision graffiti in the urban space and how they think the city through it. We used the photovoice technique to collect testimonies and the result was a plurality of visions on the images at stake.